An age-dependent population equation with diffusion and delayed birth process - G. Fragnelli (International Journal of Mathematics and Mathematical Sciences)
We propose a new age-dependent population equation which takes into account not only a delay in the birth process, but also other events that may take place during the time between conception and birth. Using semigroup theory, we discuss the well posedness and the asymptotic behavior of the solution.